Mental health of family, friends, and co-workers of COVID-19 patients in Japan. (September 2020) - Tanoue, Yuta; Nomura, Shuhei; Yoneoka, Daisuke; Kawashima, Takayuki; Eguchi, Akifumi; Shi, Shoi; Harada, Nahoko; Miyata, Hiroaki
Highlights: As the coronavirus disease 2019 (COVID-19) pandemic rages on, the mental health of both the infected and non-infected is a rising concern. We used survey data from the Japan's local government using the LINE chatbot, the messenging service with the largest number of users in Japan, to analyse the effect of having a COVID-19 patient in one's entourage on one's mental health. People with COVID-19 patients in a close setting had higher psychological distress level than those without. Out findings suggest an urgent need to prioritize the establishment and implementation of mental health and psychosocial support tailored to family, close relatives, and friends of COVID-19 patients. Abstract: As the coronavirus disease 2019 (COVID-19) pandemic rages on, the mental health of both the infected and non-infected is a rising concern. We used administrative survey data (16402 responses in the last two weeks) using a chatbot on LINE, the most popular social networking service (SNS) in Japan, to show that people with COVID-19 patients in a close setting had higher psychological distress level than those without. We believe that the results indicate an urgent need to prioritize the establishment and implementation of mental health and psychosocial support tailored to family, close relatives, and friends of COVID-19 patients.